Pregnancy in Desmin-Related Cardiomyopathy - Faksh, Arij; Codsi, Elisabeth; Barsoum, Michel K.; Brost, Brian C. (American Journal of Perinatology Reports, 2015)
The course of desmin-related restrictive cardiomyopathy (DRCM) during pregnancy has not been described previously because of the rarity of the condition. Following an episode of heart failure antecedent to conception, a 28-year-old primigravida with DRCM presented to establish prenatal care during the first trimester. Prenatal management consisted of β-blocker and diuretic therapy, with serial echocardiography to monitor cardiac function. Spontaneous labor ensued at 39 weeks' gestation, and vacuum-assisted delivery was performed for fetal indication. Postpartum blood transfusion was required for symptomatic anemia because of uterine atony, and subsequent maternal and neonatal courses were uncomplicated. Cardiac evaluation postpartum demonstrated stable maternal status. Pregnancy in women with controlled DRCM is not contraindicated, however, it requires careful planning and monitoring during the antenatal, intrapartum, and postpartum periods. On the basis of this report, pregnancy does not appear to exert a permanent deleterious effect on cardiac function in women with DRCM.
Keywords: pregnancy; desminopathy; restrictive cardiomyopathy; DES gene